Bodies of Knowledge Bodily Perfection in Tantric Buddhist Practice - Gray, David B. 1969- (2021)
This essay explores conflicting attitudes toward the body in Buddhist literature, with a focus on the tantric Buddhist traditions of yoga and meditation, which advanced the notion that the body was an innately pure site for realization while nonetheless still encumbered with earlier notions of the body as an impure obstacle to be overcome. Looking closely at a short meditation text attributed to the female Indian saints Mekhalā and Kanakhalā, the author argues that the body plays a central role in the creative re-envisioning of the self that characterizes tantric Buddhist practice.
Keywords: Buddhism; Heruka Body Mandala; Kanakhalā; Mekhalā; Yoginītantras; Body; Meditation; Non-duality; subtle body; Tantra; Yoga